Pengaruh Periode Penyimpanan Beras terhadap Pertumbuhan Populasi Sitophilus oryzae (L.) dan Kerusakan Beras - Hendrival H; Rika Muetia (Biogenesis: Jurnal Ilmiah Biologi, 2016)
The research aims to study the effect of rice storage period against the growth of Sitophilus oryzae population and weight loss characteristics of rice.  The rice storage period consists of five levels: rice storage for 40, 60, 80, 100, and 120 days.  The results showed that rice storage period affects the growth of S. oryzae population, weight loss characteristics of rice, and the percentage of rice powder. The 120-day storage period may increase S. oryzae populations, weight loss characteristics of rice, and the percentage of rice powder. The relationship between the storage period and the growth of S. oryzae population, weight loss characteristics of rice, and the percentage of rice powder increased linearly. There was a positive and very significant correlation between the rice storage period and the imago of S. oryzae population (r = 0.996**; P <0.01), weight loss percentage (r = 0.990**; P <0.01), perforated grain percentage (R = 0.994**; P <0.01), and the percentage of rice powder (r = 0.971**; P <0.01).